Coupled Effects between Solid Particles and Gas Velocities on Erosion of Elbows in Natural Gas Pipelines. (2015) - Lin, Nan; Lan, Hui-Qing; Xu, Yu-Gong; Cui, Yue; Barber, Gary
Abstract: The damage of materials caused by erosion of solid particles occurs on a large scale in different fields, including machinery, aviation, and pipeline transportation, resulting in considerable economic losses in the world. Therefore, the erosion of elbows has been extensively researched, with emphasis on single factors such as properties of solid particles, gas velocities, incidence angles, and temperatures. Erosion is generally affected by two or more coupled factors, however very few studies have been conducted on this subject. Thus, this study investigates the coupled effect between solid particles and gas velocities on the erosion of elbows in natural gas pipelines. A simulation was performed by combining the theoretical model of erosion and the Lagrange discrete phase model. The simulation result was then compared with the results of the working conditions and test platform based on a similar principle. Moreover, the properties of solid particles and the speed of natural gas in pipelines were coupled to analyze the change of erosion rate at different velocities and properties of solid particles (i.e., sizes, shapes, quantities, and incidence angles). Results showed that the erosion rate increases with the increase in size and quantity of solid particles. The small shape coefficient of solid particles causes severe erosion, and their incidence angle influences the rate and position of erosion of the elbows. A complicated coupling effect between solid particles and gas velocities on the erosion of elbows in natural gas pipelines occurs.